MATHEMATIC MODEL OF HIDROLYSIS PROCESS FROM BANANA TREES CELLULOSE TO GLUCOSE BY USING LIQUID ACID CATALYST - Silvester Tursiloadi, Galih K. Sanjaya dan Nastiti Siswi Indrasti2 (Jurnal Teknologi Industri Pertanian, 2009)
Banana trees are rich of cellulose and a potential source for producing glucose. The aim of the research was to develop a mathematic model of banana tree fiber hydrolysis by using sulfite acid as catalyst. The concentratios of the acid catalyst were 0.25 M, 0.5 M, and 1M at temperature of 85 oC and 100 oC. The concentration of acid catalyst and the reaction temperature were varied to determine the activation energy that might be affected by the addition of acid catalyst. The sugar concentration was measured as an hydrolysis parameter. The concentration of reducing sugar produced during the hydrolysis process was also measured to develop the mathematical model of hydrolysis process. The values of determination coefficient (r2) from mathematical model of kinetic reaction were more than 0.8. The kinetic model was valid for concentration range from 0.25 M to 1.5 M. Keywords: mathematical model, determination coefficient, hydrolysis, banana trees, liquid acid catalyst